The Influence of Worth Number Card Media on Mathematics Learning Outcomes Volume Unit Material for Class 5 SD Negeri 2 Labuhan Ratu Bandar Lampung City - Husna, Ukhti Masaul (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to determine whether there is an influence from the use of learning media using number card media on the learning outcomes of Mathematics in class 5B SD Negeri 2 Labuhan Ratu, Bandar Lampung City.This research is a quantitative research with the type of pre-experimental design using the one group pre-test post-test design. The population in this study were 5th grade students at SD Negeri 2 Labuhan Ratu Koata Bandar Lampung. Determination of the sample using non-probability sampling technique using a purposive sampling type, while the data collection instrument used a test. The data analysis technique used was the t-test.The results of the study were shown by the results of the t-test with a pretest-posttest score of -8.907 with a Sig. (2-tailed) 0.000 < 0.05. Which proves that there is an effect of number card media on learning outcomes.